PERBANDINGAN TOKSISITAS EKSTRAK DAUN MIMBA (Azadirachta indica A.Juss) DAN DAUN MINDI (Melia azedarach) ASAL MERAUKE TERHADAP LARVA Plutella xylostella - Prisca Rosumbre; Johana Mendes; Jefri Sembiring; R Kusumah; N Y Ekowati; Mani Yusuf (Musamus Journal of Agrotechnology Research, 2023)
Plutella xylostella is a major pest on cabbage plants. At times of hight population numbers, the larvae will eat all the leaves and leave only the bones of the leaves, this will cause severe damage, thereby reducing production yields. The result are quickly seen despite the negative impact, as a result the crops that should be of hight quality and nutrition become contaminated with chemical pesticide residues and are dangerous if consumed. The results showed that the highest mortality was in the single test of neem leaf extract, which was 57% and the highest mortality was in the mindi leaf extract which was 33%. Keywords: Mortality, Plutella xylostella, Leaves of Neem, Leaves of Mindi